Velibor Čolić’s Positioning in the French Literary Field - Sindičić Sabljo , Mirna (Anafora, 2024)
Velibor Čolić, a writer born in Bosnia and Herzegovina in 1964, has lived in France since 1992. In the 1980’s, he began to write literary texts in his mother tongue, and after going into exile, French became the privileged language of his creative expression. In his more recent prose texts, he thematizes the migrant experience that marked him existentially. Based on the hermeneutic analysis of public appearances and conversations that Velibor Čolić had with journalists from the French, Croatian, Slovenian, Montenegrin and Bosnian media, the paper examines the way in which he discursively constructs the auctorial posture of a migrant and translingual author and positions himself in the French literary field.